ANALISIS ENERGI DAN EKONOMI PLTS ON-GRID PADA RUMAH DINAS PASTORI HKBP PAPAN MAS - BEKASI - Silalahi, Eva Magdalena; Martua, David; Soebagio, Atmonobudi; Tyas Prasetyo, Antonius Dodi; Elfando, Dery (Lektrokom : Jurnal Ilmiah Teknik Elektro, 2024)
The PLTS designed in the HKBP Papan Mas official residence The PLTS designed at the HKBP Papan Mas - Bekasi Pastor's Official Residence is an on-grid PLTS with the aim of: a) designing a PLTS system based on the on-grid Solar Home System (SHS) using PVSyst software; b) determining the Break Event Point (BEP) value and the cost of electrical energy per kWh (Rp/kWh) of the on-grid PLTS; c) determining the impact of implementing PLTS on reducing CO2 emissions. From the results of the PVSyst simulation, a design for an on-grid PLTS system was obtained with a total daily electrical load of 2,419 W, namely: 8 solar modules with a capacity of 305 Wp per module, 1 unit of 6 kW inverter, with a solar module tilt angle of 14-degree.The average PLTS electrical energy is 9261.4 kWh per year, with total household electrical energy of 21,190.44 kWh/year, and a PLTS system performance ratio of 0.826/year. BEP value of on-grid PLTS 1,715 years, and the cost of electricity is Rp.286,180 per kWh. NPV value of on-grid PLTS Rp.34,159,708. Also obtained, a reduction in CO2 emissions of around 181.4 tons for 35 years of use of on-grid PLTS.